What Factors Affect Hedging? Empirical Evidance from Indonesia - Mega Barokatul Fajri; Guruh Marhaenis Handoko Putro; Jennifer Farihatul Bait; Ira Megasyara (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
This research aims to analyze each of the operational and financial factors that can be used as variables influencing decisions and the intensity of hedging. There are two test analysis model used in this study, the first to test the company decision to hedge as a measured by using dummy variables and the second model is used to test the intensity of the company in hedging as measured by the ratio of derivative and natural logarithm of derivative. By using Probit and Tobit regression, the results of the logistic regression test show that financial factors such as financial distress, and leverage, and so operational factors such as foreign sales variables did not influence the firm's decisions and intensity in carrying out hedging activities. Foreign debt variables, profitability, and firm size that include financial factors have a positive influence on company decisions and intensity in carrying out hedging decisions, while the last part of financial factors such as growth opportunity variables only has a positive effect on company decisions in carrying out hedging activities and have no effect on the intensity of firms in hedging activities. The liquidity variable has a negative influence on the decisions and intensity of the company in conducting hedging activities. The originality of this study lies in the intensity factor of the use of hedging on the company's operations and finances in hedging, whereas in previous studies only focused on the influence of factors that can influence hedging decisions.